Ascaris lumbricoides: challenges in diagnosis, treatment and prevention strategies in a European refugee camp. Issue 6 (2nd November 2018) - Claus, Paul-Emile; Ceuppens, Anne-Sophie; Cool, Mike; Alliet, Gudrun
Abstract: Objectives:  The roundworm Ascaris lumbricoides is one of the most prevalent parasites belonging to the class of the soil-transmitted helminths. Infections are most common in developing countries with a tropical climate where sanitation and hygiene are poor. However, prevalence of ascariasis in industrialized countries is increasing because of immigration and increasing number of refugees. Methods:  We report a case of ascariasis in a female patient who was admitted to our hospital after she had left the informal refugee camp of Calais in the north of France. Results:  After colonoscopic removal of the worm and treatment with mebendazole during three days the patient's symptoms had completely resolved. Medical treatment with benzimidazole derivatives is easy and inexpensive. To prevent parasitic infections in larger populations, mass drug administration should be repeated periodically and must be implemented along with additional measures such as improvements to water, sanitation and hygiene (WASH). These WASH programs have been proven to be highly effective, but access and follow-up are expensive and very difficult to organize in refugee camps, even in wealthy, industrialized countries. Conclusions: Despite being an old, well-known parasitic disease, ascariasis might reappear in certain populations at risk in industrialized countries. Detection, treatment and follow-up of these patients, and the organization of preventive measures remain challenging.